Bromatological characterization of coffee (Coffea arabica L.) pulp for animal feeding purposes - Aguirre, L. A.; Rodríguez, Zoraya; Saca, V.; Apolo, V. (Cuban Journal of Agricultural Science, 2018)
To determine the variability of the bromatological composition of coffee pulp in the province of Loja, a study was carried out by means of stratified sampling and random block design, in 18 beneficiary plants from six cantons (Espíndola, Zosoranga, Puyango, Chaguarpamba, Quilanga and Loja). Prior to the sampling, a brief characterization of production systems was carried out, through a survey to producers from the selected cantons. In the laboratory, dry matter content, organic matter, ashes, ether extract, crude protein, crude fiber and nitrogen-free extract, neutral detergent fiber and cellular content were determined. The results of the surveys showed that in 100 % of the farms, Arabian coffee of the typical variety is cultivated. There is also similarity in crop management and processing method. Regarding the bromatological analysis, no difference was observed in the nutrient content of coffee pulp among cantons, with mean values of 19.46 % for dry matter, 89.55 % for organic matter, 10.45 % for ashes, 2.23 % for ether extract, 10.02 % of crude protein, 19.24 % of crude fiber, 58.06 of nitrogen-free extract, 44.24 of neutral detergent fiber and 55.76 of cellular content. It is concluded that the bromatological composition of coffee pulp is in the ranges reported by the literature, without showing variations among the studied cantons. Therefore, this could be an interesting residue for its used as raw material for animal feeding. Keywords: agricultural residues, bromatological composition, animal feeding